Increased Akt signaling in the fat body of Anopheles stephensi extends lifespan and increases lifetime fecundity through modulation of insulin-like peptides. (October 2019) - Hun, Lewis V.; Luckhart, Shirley; Riehle, Michael A.
Graphical abstract: Highlights: Akt signaling was increased in the Anopheles stephensi fat body using the vitellogenin promoter. Increased fat body Akt activity increased ILP2 and decreased ILP3 transcript levels in the head. Increased fat body Akt activity greatly increased transcript levels of the putative insulin binding protein Imp-L2 . Akt transgenic mosquitoes had a significantly higher lifetime fecundity than non-transgenic sibling controls. Abstract: Insulin-like peptides (ILPs) and the insulin/insulin-like growth factor 1 signaling (IIS) cascade regulate numerous physiological functions, including lifespan, reproduction, immunity, and metabolism, in diverse eukaryotes. We previously demonstrated that in female Anopheles stephensi and Aedes aegypti mosquitoes, activation of the IIS cascade in the fat body led to a significant increase in lifespan. In this work, we elucidated two putative mechanisms in A. stephensi behind the observed lifespan extension and assessed whether this lifespan extension confers an overall fitness advantage to the mosquito. Specifically, we demonstrated that increased Akt signaling in the mosquito fat body following a blood meal significantly suppressed the expression of ILP2 in the head. Moreover, overexpression of active Akt in the fat body altered the expression of a putative insulin binding protein ortholog, Imaginal morphogenesis protein-Late 2 ( Imp-L2), in response to transgene expression. Combined, these two factors may act to reduce overall levels of circulating ILP2 or other ILPs in the mosquito, in turn conferring increased survival. We also examined the impact increased fat body IIS had on lifetime fecundity and demonstrated that transgenic female mosquito populations had higher lifetime fecundity relative to non-transgenic sibling controls. These studies provide new insights into the complex hormonal and molecular mechanisms regulating the interplay between IIS, aging, and reproduction in this important vector of human malaria parasites.